Hybrid systems biology : 6th International Workshop, HSB 2019, Prague, Czech Republic, April 6-7, 2019 : revised selected papers /: 6th International Workshop, HSB 2019, Prague, Czech Republic, April 6-7, 2019 : revised selected papers. ([2019]) - Unknown
No abstract available